PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE SQ3R PADA KELAS VI SDN 02 AGAK - Munir, Munir; Martono, Martono; Priyadi, Antonius Totok (Jurnal Visi Ilmu Pendidikan, 2023)
This research started from the Lesson Study PPL activity in class VI SDN 02 Agak, researchers found several problems in the process of learning activities of students in the classroom, namely (1) many students did not understand the content of the readings given. (2) the ability of students to answer questions is still below average. (3) student learning outcomes show that there are still many students who are not complete in solving the given questions. Based on the observations of researchers in the class, students have difficulty in reading understanding, this can be seen from the results of the tests carried out. A total of 16 students, only 4 students were completed. To overcome this, Class Action Research (PTK) was carried out using the SQ3R Learning Model (Survey, Question, Read, Recite, Review) to improve students' reading comprehension skills. The end result of this study is to improve reading comprehension skills and improve student learning outcomes. This research procedure goes through three cycles, namely cycles I, II and III. Each cycle is carried out through four steps as stated by Kemmis and MC. Taggart is planning, action, observation and reflection. Data collection techniques are carried out through observation, tests and documentation. The data obtained are analyzed and reflected quantitatively and qualitatively descriptively. The results showed that the S3R Model can improve student learning outcomes. The success of students in this study can be seen from the average value of each cycle that has increased. Cycle I average value 68.75, cycle II 73.25 and cycle III 78.75. In addition, the level of student learning completion increases every cycle, cycle I of completed students is 7 people or 43.75%, cycle 2 is completed by 11 people or 68.75% and cycle III is completed by 15 people or 93.75%.  Keywords: SQ3R Model, Reading Comprehension